SOSIALISASI DALAM UPAYA PENCEGAHAN PENYEBARAN COVID 19 DI AREA MESJID AL-MAHMUDAH - Nasution, Nurul Hidayah; Yaturramadhan, Hasni; Angraini, Widya; Yolandi, Silvia (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
The corona pandemic has currently hit 216 countries. The Task Force for the Acceleration of Handling Covid-19 announced that the total data on the number of positive corona cases in Indonesia until 19 May 2020 were 18,496 people. Governments in both developed and developing countries are still working to stop the spread of this new type of corona virus (SARS-CoV-2). The mosque is one of the places that can be used in an effort to socialize the prevention of the spread of covid-19. The purpose of community service so that the Al-Mahmudah congregation can easily find out information about covid-19 and efforts to prevent the spread of covid-19 in the mosque / mosque area. The socialization was carried out using posters. The population and sample of this service is the congregation of Mesjid Al- Mahmudah with a total of 40 people. The results of this community service were enthusiastically received by the congregation at the Al Mahmudah mosque which can be seen from the many employees who asked about information about efforts to prevent the spread of Covid-19 in the mosque / mosque area as well as efforts to detect, isolate and protect Covid-19 in everyday life. . It is recommended that socialization activities in an effort to prevent the spread of Covid-19 in the Al Mahmudah Mosque Area can be carried out regularly with a more frequent frequency and the range of information dissemination can also be extended to the families of the Al Mahmudah mosque congregation in general so that everyone, family and community will know more, understand more. and can practice efforts to prevent the spread of covid-19 in the mosque / musholla area as well as efforts to detect, isolate and protect Covid-19 in everyday life which can ultimately improve the degree of public health